Tinjauan Aplikasi Teknik Spektroskopi dalam Identifikasi dan Karakterisasi Senyawa Kimia Bahan Alam secara Efisien - Nabila Sativa; Nailia Nur Isma Sumarno; Rusnia Apriliana; Laohannia Challiztha; Gabriyuvella Gabriyuvella; Syifa Askila Rahmadani; Yenni Hafizah (An-Najat, 2025)
This review discusses the application of various spectroscopic methods such as UV-Vis, FTIR, NMR, and GC-MS in the isolation and identification of secondary metabolites from natural products. The use of these spectroscopic techniques is crucial in the field of natural product chemistry as they provide accurate information about the structure, composition, and presence of bioactive compounds without destroying the sample. UV-Vis spectrophotometry is widely used for quantifying compounds such as flavonoids, saponins, tannins, and alkaloids in various plant species, including chili, okra, ridge gourd, and Averrhoa bilimbi leaves. This method is known for being fast, simple, and sufficiently sensitive for both qualitative and quantitative determination of phenolic and antioxidant compounds. FTIR spectroscopy is utilized to identify functional groups in plant extracts such as rose apple, noni fruit, red ginger, bay leaves, and red spinach. The results indicate the presence of phenolic compounds, flavonoids, and alkaloids through the identification of characteristic absorption bands from hydroxyl, carbonyl, methyl, and amine groups. FTIR is also useful for evaluating the purity and consistency of extracts. Mass spectrometry (MS), particularly GC-MS, is applied to determine the chemical profiles of essential oils and plant extracts such as citronella, Urena lobata, and Libo plants. Major compounds identified include zingiberene, citronellal, citronellol, digitoxigenin, and various terpenoids. This technique is highly effective in detecting volatile and semi-volatile compounds with high sensitivity. Meanwhile, NMR spectroscopy is employed to elucidate the structure of complex compounds such as xanthones and their derivatives, either from natural sources like endophytic fungi or from synthetic processes. NMR is essential for determining the three-dimensional structure and stereochemistry of molecules. This review highlights that a combinative approach involving multiple spectroscopic techniques is highly effective in rapidly and accurately identifying the structure and composition of active compounds in natural product research. The integration of these techniques represents a strategic approach to support the discovery and development of natural product-based drugs in the future.